Formulation of a sheet mask essence incorporating Betel leaf (Piper betle L.) ethanol extract and its antibacterial efficacy against Propionibacterium acnes - Wulandari, Annisa Dyah; Sunarto, Sunarto; Kurniawan, Dhadhang Wahyu (Universitas Ahmad Dahlan, 2025)
Betel leaf (Piper betle L.) encompasses a multitude of bioactive constituents, including tannins, saponins, flavonoids, alkaloids, and terpenoids, which possess significant antibacterial properties. An ethanol extract derived from betel leaf was meticulously formulated and assessed for its potential as an antibacterial agent specifically targeting Propionibacterium acnes, a bacterium associated with the etiology of acne. This investigation was undertaken with the aim of mitigating the antibiotic resistance commonly observed with traditional acne therapies. The ethanol extract of betel leaf was incorporated into a sheet mask essence, resulting in the development of four distinct formulations (F0, F1, F2, and F3), which were subsequently subjected to comprehensive evaluations of their physical quality and stability. The formulation exhibiting optimal physical characteristics and stability was further scrutinized for its antibacterial efficacy against Propionibacterium acnes. The antibacterial performance of the selected formulation was benchmarked against a positive control comprising a sheet mask infused with clindamycin gel, as well as another containing tea tree oil. Empirical results identified Formula 2, containing 1.5% ethanol extract of betel leaf, as the most efficacious formulation. Formula 2 demonstrated pronounced antibacterial activity against Propionibacterium acnes, with an inhibitory zone measuring 24.67 mm. Although this inhibitory zone was slightly less extensive than that produced by the clindamycin gel sheet mask (32.00 mm), it was comparable to the tea tree oil sheet mask, which exhibited an inhibitory zone of 23.00 mm. In conclusion, the selected sheet mask formulation (Formula 2) exhibits significant antibacterial activity against Propionibacterium acnes, surpassing the efficacy of commercially available tea tree oil sheet masks, thereby presenting a promising alternative for acne management with a diminished risk of promoting antibiotic resistance.